Ultrathin Limit on the Anisotropic Superconductivity of Single-Layered Cuprate Films - Ran, Feng; Chen, Pan; Li, Dingyi; Xiong, Peiyu; Fan, Zixin; Ling, Haoming; Liang, Yan; Zhang, Jiandi (Chinese physics letters, 2024)
Exploring dimensionality effects on cuprates is important for understanding the nature of high-temperature superconductivity. By atomically layer-by-layer growth with oxide molecular beam epitaxy, we demonstrate that La 2– x Sr x CuO 4 ( x = 0.15) thin films remain superconducting down to 2 unit cells of thickness but quickly reach the maximum superconducting transition temperature at and above 4 unit cells. By fitting the critical magnetic field ( μ 0 H c2 ), we show that the anisotropy of the film’s superconductivity increases with decreasing film thickness, indicating that the superconductivity of the film gradually evolves from weak three- to two-dimensional character. These results are helpful to gain more insight into the nature of high-temperature superconductivity with dimensionality.